Tricuspid Valve Avulsion after Blunt Chest Trauma - Mehrotra, Deepak (Texas Heart Institute, 2012)
Blunt cardiac trauma causing tricuspid regurgitation is rare and is most often associated with traffic accidents. Falling from a height can also cause such injuries, resulting in hemodynamic compromise and arrhythmias. The signs of traumatic tricuspid regurgitation can appear early or be delayed, depending upon the severity of injury. We present the case of a 68-year-old woman who fell from a height onto rocks during a hike. She sustained blunt cardiac injury with complete tricuspid valve avulsion, and underwent successful repair. In addition, we review the relevant medical literature.